Identification of lncRNA Signature of Tumor-Infiltrating T Lymphocytes With Potential Implications for Prognosis and Chemotherapy of Head and Neck Squamous Cell Carcinoma - Wang, Liping; Yang, Gui; Liu, Guohong; Pan, Yunbao (Frontiers in Pharmacology, 2022)
Abstract Purpose: We systematically analyzed paired HNSCC-infiltrating T lymphocytes lncRNAs (HILTlncRNAs) to assess their predictive value for the survival outcome and immunotherapy response of patients with anti-programmed death-1 (PD-1) therapy and to evaluate their predictive power to chemotherapeutic agents. Methods: HNSCC transcriptome and clinical information was obtained from The Cancer Genome Atlas (TCGA) database. Immunocell microarray data were obtained from the Gene Expression Omnibus (GEO) database. T-cell-specific lncRNAs were identified by differential expression analysis. Prognostic paired HILTlncRNAs (PHILTlncRNAs) were filtered and modeled by univariate cox, lasso and multivariate cox regression analysis. To construct lncRNA-miRNA-mRNA competitive endogenous RNA (ceRNA) regulatory networks, differentially expressed mRNAs in HNSCC patients were incorporated, microRNAs and differentially expressed mRNAs interacting with T-cell-specific lncRNAs were filtered out based on miRcode, miRDB, miRTarBase, and TargetScan databases. . Results: 75 T-cell-specific lncRNAs and 9 prognostic PHILTlncRNAs were identified. Low-risk HNSCC patients had a better prognosis and significant immune cell infiltration, driving the immune response. Differential expression of RNA-binding proteins (RBPs), PD-1 and programmed cell death 1 ligand 1 (PD-L1) was demonstrated in the high and low risk groups of HNSCC patients. In the high risk group, high expression of PD-1 improved patient prognosis, whereas the opposite was observed in the low-risk group. The promoter methylation levels of two RBPs (DNMT1 and ZC3H12D) were decreased in HNSCC patients compared with normal samples, their expression levels were positively correlated with PD-1 and PD-L1 levels and T-cell infiltration. Finally, we screened the sensitivity of HNSCC patients to chemotherapeutic agents and found it differed between high and low risk groups. Conclusion: PHILTlncRNAs provided a theoretical basis for immune targeted therapy and drug development.